Stereoselective synthesis of (2S,7S)-7-(4-phenoxymethyl)2-(1-N-hydroxyureidyl-3-butyn-4-yl)oxepane: a potential anti-asthmatic drug candidate - Gurjar, M. K.; Rao, B. V.; Krishna, L. M.; Chorghade, Mukund S.; Ley, S. V. (Tetrahedron-Asymmetry, 2005)
We have achieved a short, efficient stereoselective synthesis of 7-membered oxepane derivatives with potential against asthma. Highlights of our synthetic strategy are regioselective oxidation of a hydroxyl group and efficient ring closure of an open chain aldehyde to a 2-benzenesulfonyl oxepane derivative with PhSO2H. Surprisingly the cis-isomer showed better activity than the traps-isomer. (C) 2005 Elsevier Ltd. All rights reserved.